1995
DOI: 10.1007/bf00210408
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of linkage to 1q21-31 in a Danish autosomal dominant juvenile-onset glaucoma family and evidence of genetic heterogeneity

Abstract: Autosomal dominant juvenile-onset open-angle glaucoma has been mapped to 1q21-31 in a number of American families. Our study confirms linkage in a Danish five-generation dominant juvenile-onset glaucoma family with a maximum two-point lod score of 6.67 at the D1S210 locus. Multipoint linkage analysis in a nine-generation Swedish family with dominant juvenile-onset glaucoma and iris hypoplasia excludes linkage to the region of approximately 18 cM between loci D1S104 and D1S218, shown to contain the previously m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 11 publications
3
20
0
2
Order By: Relevance
“…Recently, a susceptibility gene termed GLC1A was localized on chromosome 1q21-q31 in a large American family (Sheffield et al 1993). This essential finding was confirmed by subsequent studies (Richards et al 1994;Wiggs et al 1994;Graff et al 1995;Morissette et al 1995).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, a susceptibility gene termed GLC1A was localized on chromosome 1q21-q31 in a large American family (Sheffield et al 1993). This essential finding was confirmed by subsequent studies (Richards et al 1994;Wiggs et al 1994;Graff et al 1995;Morissette et al 1995).…”
Section: Introductionsupporting
confidence: 75%
“…Clinically, they seem to fall into one of two categories when considering the age at onset of disease. In the first category of six families, glaucoma consistently begins before the age of 20 years (Sheffield et al 1993;Richards et al 1994;Wiggs et al 1994;Graff et al 1995) and the penetrance of the disease gene is complete or almost complete. Three ocular hypertensive obligate carriers were nevertheless identified in the family described by Johnson et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of pedigrees with iris hypoplasia in addition to juvenile/early onset autosomal dominant glaucoma, similar to those previously described by other authors,23 24 have failed to show linkage to 1q21-q31, suggesting a genetic as well as phenotypic difference 5677 Recently, two autosomal dominant pedigrees with features of iris hypoplasia, goniodysgenesis, and juvenile glaucoma, termed the iridogoniodysgenesis anomaly, were mapped to an 8.3 cM region on chromosome 6, 6p25 78.…”
Section: Genetics Of J-poagsupporting
confidence: 61%
“…20 22 A number of papers, which demonstrate linkage of J-POAG pedigrees with 1q21-q31, commented that the drainage angles and/or trabecular meshwork appeared normal 1950 51 However, a Danish pedigree, linked to 1q21-q31, has been described, in which gonioscopy showed various signs of goniodysgenesis—for example, high insertion of the iris, a grey membrane overlying the trabecular meshwork, and an abnormally exposed greater arterial circle of Willis, but no evidence of iris hypoplasia 56. The authors suggested that the absence of goniodysgenesis in other reported families needs to be explained.…”
Section: Genetics Of J-poagmentioning
confidence: 99%
“…Several pedigrees with JOAG and dominant autosomal heredity have been described (Bell 1932;Jerndal 1970;Lichter 1994). Pedigrees with JOAG have been linked to chromosome 1q, GLC1A (Sheffield et al 1993;Wiggs et al 1994;Richards et al 1994;Meyer et al 1994;Graff et al 1995;Morissette et al 1995;Meyer et al 1996;Johnson et al 1996;Lichter et al 1997) and 6p (Mears et al 1996;Graff et al 1997). The two latter pedigrees show heterogeniety with the other ones.…”
mentioning
confidence: 99%